Identifikasi Persepsi Dosen dan Mahasiswa Terhadap Pembelajaran Berbasis Website (PBW) di Prodi Pendidikan Matematika FTK UIN Suska Riau - Musa Thahir; Yenita Roza; Atma Murni (Universitas Hamzanwadi, 2018)
This article is based on the limited lecture model for Kapita Selekta Mathematics (KSM) courses. The purpose of writing this article is to identify the perception of lecturers and students to PBW in Prodi PMT FTK UIN Suska Riau seen from: 1) the existence of math-based learning website; 2) understanding of lecturers and students regarding the existence of PBW; and 3) problems in implementing PBW. This article uses quantitative descriptive research. The subjects involved consisted of three lecturers and seven students. Data were collected through PBW utilization questionnaires. Data were analyzed using quantitative descriptive. This article presents some conclusions, among others: 1) lecturers and students do not understand the importance of PBW; 2) PBW has the advantage and good quality in supporting the learning process of mathematics; and 3) the main problem in implementing PBW is infrastructure especially in WiFi /hotspot facility and lecturer's ability